Present‐day kinematics of the East African Rift. Issue 4 (7th April 2014) - Saria, E.; Calais, E.; Stamps, D. S.; Delvaux, D.; Hartnady, C. J. H.
<x xml:space="preserve">Abstract</x> The East African Rift (EAR) is a type locale for investigating the processes that drive continental rifting and breakup. The current kinematics of this 5000 km long divergent plate boundary between the Nubia and Somalia plates is starting to be unraveled thanks to a recent augmentation of space geodetic data in Africa. Here we use a new data set combining episodic GPS measurements with continuous measurements on the Nubian, Somalian, and Antarctic plates, together with earthquake slip vector directions and geologic indicators along the Southwest Indian Ridge to update the present‐day kinematics of the EAR. We use geological and seismological data to determine the main rift faults and solve for rigid block rotations while accounting for elastic strain accumulation on locked active faults. We find that the data are best fit with a model that includes three microplates embedded within the EAR, between Nubia and Somalia (Victoria, Rovuma, and Lwandle), consistent with previous findings but with slower extension rates. We find that earthquake slip vectors provide information that is consistent with the GPS velocities and helps to significantly reduce uncertainties of plate angular velocity estimates. We also find that 3.16 Myr MORVEL average spreading rates along the Southwest Indian Ridge are systematically faster than prediction from GPS data alone. This likely indicates that outward displacement along the SWIR is larger than the default value used in the MORVEL plate motion model.